Assessment of the Knowledge and Practices about Diabetes Mellitus among Governmental School Teachers in Uglat Asugour, Qassim, Saudi Arabia - Almohaileb, Faisal Ibrahim; Alturki, Omar Ahmed; Alsudays, Ali Mohammed; Aldakheel, Ibrahim Abdulkareem; Alarfaj, Ali Abdulrahman (International Journal of Innovative Research in Medical Science, 2020)
Background: Knowledge and practice about diabetes mellitus (DM) are crucial among school teachers as they could not only be diabetic, dealing with diabetic children/adolescents, but they also share the responsibility of improving the awareness and practice regarding the epidemic disease in our community. Objectives: This cross-sectional study was done in a rural area, Uglat Asugour, to determine the awareness and practices considering DM among governmental school teachers, and, their relationship with teachers' sociodemographic, life style, and anthropometric indices, and, their history of DM. Furthermore, the study aimed to compare between awareness and practice among study participants and to identify risk factors and their relationship. Participants and Methods: The study anonymously enrolled all the voluntarily willing elementary, middle and high school male teachers during April 2018. Data collection tool was a structured self-administered Arabic-language questionnaire that contained a part for collection of the sociodemographic, life style and anthropometric characteristics and diabetes medical history of participants, part 2 has 15 items concerned with knowledge, and, part 3 has 4 items concerned with practice regarding DM. Absentees for any reason were excluded. Results: A total of 171 teachers were targeted. The response rate was 91.8% meaning that 157 teachers were included. Their age was 33.5 ± 06.4 (mean ± SD) years. 5.1% were diabetic and 31.8% of them were having diabetic student(s). The knowledge regarding DM among them showed that 141 (89.8%) had good knowledge and only 16 (10.2%) were having poor knowledge. In regard to practice, 106 (67.5%) teacher were having good practice while 51 (32.5%) were having poor practice. Diabetic teachers and those with a family member with DM, ex-teachers on administrative jobs and teachers at elementary schools scored better than the others in both aspects. Conclusion: comparable to national and international reports, the majority of the targeted school teachers showed a good knowledge and exhibited a good practice regarding DM. Because the country suffers a diabetes epidemic, knowledge and practice require furthering programs that target school teacher in particularly.